2013
DOI: 10.1080/87565641.2013.805218
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Correlates of Auditory and Language Development: A Mismatch Negativity Study

Abstract: During child development, physiological changes occur in the auditory cortex, which are reflected by differences in the electrophysiological signals. This study aimed to examine the age-related changes of the Mismatch Negativity component (MMN) in response to speech and non-speech stimuli in a cross-sectional design. Results revealed distinct patterns of activation according to stimulus type and age. Age-related differences for tone discrimination occurred earlier in children's development than did the discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…()]. Children's MMNs resemble adult responses for easily discriminable contrasts, with latencies varying between 100 ms and 400 ms, depending on age, stimulus type, and magnitude of change (Shafer et al ., ; Paquette et al ., ) [for a review, see Näätänen et al . ()].…”
Section: Introductionmentioning
confidence: 99%
“…()]. Children's MMNs resemble adult responses for easily discriminable contrasts, with latencies varying between 100 ms and 400 ms, depending on age, stimulus type, and magnitude of change (Shafer et al ., ; Paquette et al ., ) [for a review, see Näätänen et al . ()].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, an exhaustive neuropsychological battery testing all components of memory (declarative and procedural), attention (auditory and visual), and language (receptive and expressive), as well as academic skills would gain from the inclusion of an MMN assessment. MMN responses can be reliably recorded early in life, including in newborns, and MMN responses to speech discrimination are homogenous within specific age ranges . After detecting weaknesses and strengths of the child, an individually tailored intervention project has to be started as soon as possible, since the link between auditory dysfunction and developmental disorders is widely recognized, even in nonepileptic children (for a review, see).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, especially in atypical 33 and MMN responses to speech discrimination are homogenous within specific age ranges. 34 After detecting weaknesses and strengths of the child, an individually tailored intervention project has to be started as soon as possible, since the link between auditory dysfunction and developmental disorders is widely recognized, even in nonepileptic children (for a review, see 35 ). Moreover, during the so-called critical or sensitive period, the neural substrate for the skill to be acquired is most malleable, and missing the correct time to learn will result in poor mastering of that skill.…”
Section: Figurementioning
confidence: 99%
“…Our results thus contribute to the understanding of cerebral development through childhood and adolescence in regions specifically devoted to language production. A growing number of studies have reported distinct patterns of brain activation in children, adolescents, and adults, notably regarding the development of language function (Gogtay et al, 2004;Luna et al, 2001;Moore and Linthicum, 2007;Paquette et al, 2013;Porter et al 2011). In a study assessing the relationship between language abilities and cortical thickness across development, Porter et al (2011) found a significant relationship between increasing speech fluency skills and decreasing cortical thickness in regions involved in the language network, such as Wernicke's and Broca's areas and the perisylvian regions.…”
Section: Groups (N)mentioning
confidence: 95%
“…Based on previous developmental studies (Bishop et al, 2011;Paquette et al, 2013), and in order to reflect their developmental cognitive stage (Piaget and Inhelder, 1969;Piaget, 1972), children were grouped into three age ranges covering different developmental stages: early childhood or preschool age (3-6 years old, n ¼10), late childhood or school age (7-10 years old, n ¼10) and adolescence (11-16 years old, n ¼12). In order to identify the age range in which lateralization patterns of expressive language functions adopt the adult pattern, 11 French-speaking young adults (19-30 years old, five males/six females) were also recruited.…”
Section: Participantsmentioning
confidence: 99%